Abnormal hsa_circ_0003948 expression affects chronic periodontitis development by regulating miR‐144‐3p/NR2F2/PTEN signaling - Li, Wei; Zhang, Zhi; Li, Yizi; Wang, Zuomin (Journal of periodontal research, 2022)
Background and Objective This study aimed to investigate the correlation between chronic periodontitis (CP) and abnormal circular RNA (circRNA) expression and to identify the role of hsa_circ_0003948 in the progression of CP. Methods Next‐generation sequencing was utilized to investigate abnormal expression of circRNA in gingival tissues from CP patients and healthy control subjects. Bioinformatics and luciferase reporting analyses were used to clarify the interactive relationship among circRNA, miRNA, and mRNA. Periodontal ligament cells (PDLCs) were employed to analyze proliferation and apoptosis after lipopolysaccharide (LPS) treatment using the cell counting kit 8 (CCK8) assay and flow cytometry detection. Results High‐throughput sequencing and RT‐qPCR analyses confirmed that hsa_circ_0003948 expression decreased dramatically in gingival samples of CP patients. Overexpression of hsa_circ_0003948 alleviated LPS‐induced PDLC injury by regulating NR2F2/PTEN signaling. The miR‐144‐3p and NR2F2 were determined to be hsa_circ_0003948 downstream targets. NR2F2 downregulation or miR‐144‐3p overexpression reversed the protective effect of hsa_circ_0003948 in PDLCs after treatment with LPS. Upregulation of NR2F2 reversed the inhibitory effect of miR‐144‐3p on surviving PDLCs after LPS treatment. Conclusion Overexpression of hsa_circ_0003948 exerts a protective effect in CP via miR‐144‐3p/NR2F2/PTEN signaling regulation.